Implementation of Internal Control in Recording Inventory at CV Madona Ponsel - Endang Wijayanti Mendrofa; Serniati Zebua; Maria Magdalena Bate'e; Kurniawan Sarototonafo Zai (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the implementation of internal control in the inventory recording system at CV Madona Ponsel. The research was conducted to identify the effectiveness of the company's internal control procedures, especially in the use of stock cards, hybrid recording methods, and verification processes for incoming and outgoing inventory. A qualitative descriptive method was applied, with data collected through interviews, observations, and documentation. The results revealed that the company has implemented internal control elements such as authorization, separation of duties, supervision, and stock reconciliation. However, weaknesses were found in documentation consistency, the absence of computerized integration, and reliance on manual stock cards, which often leads to delays, errors, and discrepancies between physical stock and recorded stock. The study concludes that although the internal control system is generally effective, it requires improvement in record accuracy, supervision mechanisms, and technological adoption to prevent errors and fraud. Strengthening internal control is essential to maintain inventory accuracy, support operational efficiency, and ensure reliable financial reporting.